2020
DOI: 10.3390/ijerph17103350
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Maternal Functioning between Iranian Mothers with and without Depressive Symptoms: A Case-Control Study

Abstract: Postpartum depression (PPD) has adverse effects on the mother’s ability to work, her relationships, performance in other roles, and caregiving ability. The aim of this study was to compare levels of maternal functioning between mothers with depression symptoms and those without. The participants of this case-control study included 80 postpartum women (n = 40 with depressive symptoms and n = 40 with no depressive symptoms) referred to health centers in Tabriz, Iran, in 2018–2019. The case and control groups wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
(53 reference statements)
0
9
1
1
Order By: Relevance
“…A flow diagram summarizing the 46 included studies and PROMs evaluated in this review is provided in the Figure . 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 There were 1277 postpartum studies registered with ClincalTrials.gov, none of which were validation studies for any of the identified PROMs. Three PROMs from the previous scoping review were excluded (1 required free-text responses, and 2 evaluated multiple domains primarily associated with sexual function rather than overall postpartum recovery).…”
Section: Resultsmentioning
confidence: 99%
“…A flow diagram summarizing the 46 included studies and PROMs evaluated in this review is provided in the Figure . 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 There were 1277 postpartum studies registered with ClincalTrials.gov, none of which were validation studies for any of the identified PROMs. Three PROMs from the previous scoping review were excluded (1 required free-text responses, and 2 evaluated multiple domains primarily associated with sexual function rather than overall postpartum recovery).…”
Section: Resultsmentioning
confidence: 99%
“…There were no significant differences in sociodemographic data between the case and control groups. The socio-demographic characteristics of the participants have been reported in another article (12).…”
Section: Resultsmentioning
confidence: 99%
“…This study was a part of a large case-control study with the code of ethics IR.TBZMED.REC.1398.218, and the results of other parts of the study have been published previously (12). This study was conducted from February 2019 to May 2019 among 80 postpartum women admitted to Tabriz health centers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of the relevant studies conducted in other countries suggested that the frequency of PPD was distributed in a wide range from 0.6% to 60.8%. In general, it was reported that approximately one in 7-10 mothers in the world had an increased risk of PPD [11][12][13].…”
Section: Discussionmentioning
confidence: 99%